Clerical Conformity and the Elizabethan Settlement Revisited - Marshall, Peter (The historical journal, 2016)
This article re-examines the nature and extent of conformity to the Religious Settlement amongst the parish clergy in the first decades of Elizabeth I's reign. The estimate of Henry Gee, made over a century ago, that only around 300 clergymen were deprived for non-conformity to the Settlement has been remarkably influential and durable, and it continues to shape broader assessments of the ways in which religio-political change was implemented and received in this period. Using digital resources such as the Clergy of the Church of England Database, in conjunction with hitherto neglected biographical compilations, the article argues for a significant revision of Gee's figures. More broadly, it reflects on the complex meanings of ‘conformity’ in a period of perplexing change and dramatic institutional disruption, disputing any suggestion that apparent acquiescence signalled pervasive ‘acceptance’ of the alteration in religion among the clergy. In the process, it draws attention to the pitfalls of uncritical deployment of numbers and statistics, and of using them as explanatory short-cuts in understanding the dynamics of Reformation change.